Analysis of Trends and Composition of Forest and Vegetative Land Rehabilitation Activities in the Limboto Lake Catchment Area for the Period 2021-2025 - Sitti Mutiah Rahman; Iswan Dunggio; Sukirman Rahim (Westscience Press, 2026)
This study analyzes the temporal trend and activity composition of vegetative forest and land rehabilitation (RHL) in the catchment area of Lake Limboto for 2021–2025. A quantitative descriptive approach was applied to secondary data from the BPDAS Bone Limboto 2025 database, strengthened with year-on-year change rates, the coefficient of variation, concentration ratios, and the Herfindahl-Hirschman index to assess the program portfolio structure. The total area of vegetative RHL over five years reached 693 ha, with an annual mean of 138.6 ha and a coefficient of variation of about 79.9%, indicating a dynamic, phase-based implementation rhythm. The highest achievement occurred in 2022 (340 ha; 49.06%), while the two leading years (2022–2023) accounted for 74.31% of the total. By composition, core RHL planting dominated (262 ha; 37.81%), followed by watershed rehabilitation (200 ha; 28.86%) and the Community Nursery/KBR (183 ha; 26.41%); these three pillars formed 93.07% of the portfolio, with an effective number of activities of 3.33. The annual composition revealed a tiered pattern from seedling provision toward larger-scale planting. Spatial interpretation of the activity map showed interventions concentrated on the buffer hill belts to the north, west, and south of the catchment, consistent with an upstream-priority logic. The findings emphasize that RHL evaluation should consider temporal continuity and compositional balance, not only area achievement.